2020
DOI: 10.3389/fnins.2020.00693
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Pathways of COX-2 and mTOR: Roles in Cell Sensing and Alzheimer’s Disease

Abstract: Cyclooxygenases (COX) are enzymes catalyzing arachidonic acid into prostanoids. COX exists in three isoforms: COX-1, 2, and 3. COX-1 and COX-2 have been widely studied in order to explore and understand their involvement in Alzheimer's disease (AD), a progressive neuroinflammatory dementia. COX-2 was traditionally viewed to be expressed only under pathological conditions and to have detrimental effects in AD pathophysiology and neurodegeneration. However, an increasing number of reports point to much more comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 167 publications
(237 reference statements)
3
19
0
Order By: Relevance
“…This result can also be supported by a previously reported study carried out by Nomura and co-workers whereby they demonstrated that the hydrolysis of 2-AG and AEA generated arachidonic acid (AA) in the brain, which is a major precursor for the COX-mediated biosynthesis of prostaglandins that promote neuroinflammation . 2-AG mediated its response by activating CB1 receptors, which inhibit phosphorylation of the ERK1/p38MAPK/NF-κB pathway and therefore reduce the expression of the COX enzyme. , Moreover, an increase in the pro-inflammatory cytokine level in the brain is also linked to the free radical formation and mitochondrial dysfunction in neurodegenerative diseases . Corresponding to these findings of increased oxidative stress due to STZ injection in the brain, we also determined the levels of TBARS, CAT, and SOD.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This result can also be supported by a previously reported study carried out by Nomura and co-workers whereby they demonstrated that the hydrolysis of 2-AG and AEA generated arachidonic acid (AA) in the brain, which is a major precursor for the COX-mediated biosynthesis of prostaglandins that promote neuroinflammation . 2-AG mediated its response by activating CB1 receptors, which inhibit phosphorylation of the ERK1/p38MAPK/NF-κB pathway and therefore reduce the expression of the COX enzyme. , Moreover, an increase in the pro-inflammatory cytokine level in the brain is also linked to the free radical formation and mitochondrial dysfunction in neurodegenerative diseases . Corresponding to these findings of increased oxidative stress due to STZ injection in the brain, we also determined the levels of TBARS, CAT, and SOD.…”
Section: Discussionsupporting
confidence: 85%
“…61 2-AG mediated its response by activating CB1 receptors, which inhibit phosphorylation of the ERK1/p38MAPK/NF-κB pathway and therefore reduce the expression of the COX enzyme. 62,63 Moreover, an increase in the pro-inflammatory cytokine level in the brain is also linked to the free radical formation and mitochondrial dysfunction in neurodegenerative diseases. 38 Corresponding to these findings of increased oxidative stress due to STZ injection in the brain, we also determined the levels of TBARS, CAT, and SOD.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have depicted the role of COX-2 in inflammation and AD. 45 In line with a previous study, 46 our results showed that contrary to COX-2 which was elevated upon LPS stimulation, the COX-1 mRNA and protein levels in the BV-2 cells were decreased after the LPS treatment. Conversely, some studies also reported that COX-1 is activated by LPS in PC12 cells.…”
Section: Discussionsupporting
confidence: 91%
“…COX-2 is stimulated by inflammatory components such as cytokines, TNF-α, IL-1, and IL-2 and has been documented for its combined expression in some cell masses of the brain [ 47 ]. Studies reported that COX-2 expression is deficient in astrocytes [ 48 ], increases in the early phases of the disease [ 47 , 48 ], and is principally expressed in pyramidal neurons [ 49 ].…”
Section: Neuroinflammatory Markers In the Pathogenesis Of Neurodegene...mentioning
confidence: 99%